Regulation of food product labelling in Indonesia - Nur Husni Emilson,; Made Warka,; Krisnadi Nasution, (Technium Social Sciences Journal, 2021)
This research uses normative legal research. The ratio legis of labeling food products in Indonesia in an effort to provide legal protection to the public is as regulated in Law Number 8 of 1999 concerning Consumer Protection, Law Number 7 of 1996 concerning Food, Government Regulation Number 69 of 1999 concerning Food Labels and Advertising, Decree of the Minister of Health Number 924/Menkes/SK/VIII/1996 concerning the Inclusion of "Halal" on Food Labels, Regulation of the Minister of Health of the Republic of Indonesia No. 180/Menkes.Per/IV/1985 concerning Expired Food which has been amended by Decree of the Director General of POM No. 0259 /B/SK/VIII/91. However, the implementation is not optimal. There are still obstacles in its implementation, where administrative sanctions are rarely imposed by the government on producers. The government still relies on consumer initiatives to blame it. The government seems to make this administrative sanction the ultimum remedium, because it’s associated with labor and tax considerations. Of course, these two considerations shouldn’t be ala and forgiving for entrepreneurs who harm consumers, as long as they are supported by sufficient evidence.